Acquisition and loss of nationality : policies and trends in 15 European states. - Bauböck, Rainer; Ersbøll, Eva; Groenendijk, C. A.; Waldrauch, Harald (IMISCOE research., 2006)
Detailed study of each country's nationality laws, their historical background and current provisions in 15 member states of the EU, executed by the renowned IMISCOE network.